Colored television [large type] - Senna, Danzy (Thorndike Press large print Black voices., 2025)
"A brilliant dark comedy about second acts, creative appropriation, and the racial identity-industrial complex. Jane has high hopes her life is about to turn around. After years of living precariously, she, her painter husband, Lenny, and their two kids have landed a stint as house sitters in a friend's luxurious home high in the hills above Los Angeles, a gig that coincides magically with Jane's sabbatical. If she can just finish her latest novel, Nusu Nusu, the centuries-spanning epic Lenny refers to as her "mulatto War and Peace," she'll have tenure and some semblance of stability and success within her grasp. But things don't work out quite as hoped. In search of a plan B, like countless writers before her Jane turns her desperate gaze to Hollywood. When she finagles a meeting with a hot young producer with a seven-figure deal to create "diverse content" for a streaming network, he seems excited to work with a "real writer" to create what he envisions as the greatest biracial comedy ever to hit the small screen. Things finally seem to be going right for Jane--until they go terribly wrong"--